Aafiyat Holdings Sdn Bhd / Zainah ‘Awathif Mohd Zuki - Mohd Zuki, Zainah ‘Awathif (Universiti Teknologi MARA, Perlis, 2024)
This internship report explores my six-month experience working as a marketing intern at Aafiyat Holdings Sdn Bhd, which lasted 24 weeks from 1 September 2023, to 9 February 2024. The primary market for Aafiyat Holdings' high-end natural and organic product sourcing and distribution activities is the health and wellness industry. I gained important knowledge and actively participated with Aafiyat Holdings during this experience, which was an excellent start to my career. Even though I studied human resource management, this internship gave me a ton of marketing-related experience too. I took part in marketing-related tasks, such as marketing campaigns, event committee duties and sales promotions. I improved my communication abilities by interacting with agents and employees in the office and warehouse. I provide in-depth details about Aafiyat Holdings Sdn Bhd in this report, covering information on the company's history, vision, mission, logo, organizational structure, and the variety of products and services it provides. Moreover, I perform SWOT and PESTEL analysis to evaluate the company's internal and external aspects as well as its current and future growth potential. A discussion and recommendations are provided for Aafiyat Holdings in the report as well. I describe the tasks, challenges and experiences I had while working at Aafiyat Holdings from the very beginning in the section on training reflection that follows. In conclusion, working as an intern with Aafiyat Holdings was not only rewarding but also fun. I made wonderful moments with my supportive coworkers in this highly respected organization while gaining significant knowledge and perspectives. In my current position as a trainee at Aafiyat Holdings, I look forward to remembering these priceless moments.